'Fred, it's a mess': Fred Dagg and the cultural politics of the laconic. Issue 1 (2nd January 2019) - Holm, Nicholas
Abstract: Writing on 'The New Zealand Sense of Humour' in his posthumously published book, Tinkering, John Clarke describes the comic temperament of his country of birth as 'laconic, under-stated and self-deprecating' (2017, 31). In evoking the laconic as a marker of national comic character, Clarke is far from alone: the term is frequently used as an easy, ready-to-hand account of the comic characteristics of both Clarke's native New Zealand and Australia, where he found his later comic success. Yet the ease with which the term is conjured belies the complexity of the comic forms to which it refers. Literally, 'laconic' refers to the use of few words, but it is not always clear how this definition informs laconic humour. This article explores how the laconic might be understood by examining John Clarke's comedy with particular reference to his Fred Dagg persona. It argues that Dagg's presentation of the laconic can be productively understood in opposition to Sianne Ngai's account of the 'zany'. This comparison brings to light the affective elements of the laconic, seen as character-based comedy premised on the absence of care or attention. Understood through this lens, Dagg's laconic comedy appears as comic engagement with the emotional repression and affective apathy that has historically been associated with New Zealand provincial communities.